Surgery for Anomalous Aortic Origin of Coronary Arteries: Technical Safeguards and Pitfalls - Padalino, Massimo A.; Jegatheeswaran, Anusha; Blitzer, David; Ricciardi, Gabriella; Guariento, Alvise (Frontiers in Cardiovascular Medicine, 2021)
Anomalous aortic origin of a coronary artery (AAOCA) is a congenital heart defect which has been reported as the second leading cause of sudden cardiac death in otherwise healthy young individuals. Several surgical studies have reported a very low operative risk, describing repair as safe and effective with short or medium-term follow-up. However, surgical repair can also be associated with a high risk of complications. Numerous repair techniques have been described in the literature, but the indications and limitations of each technique are often not well understood or understated. Since clear technical knowledge of the most appropriate surgical technique is highly desirable, we sought to thoroughly and clearly outline the safeguards and pitfalls of the most common surgical techniques used for the repair of AAOCA.